2012
DOI: 10.3762/bjoc.8.65
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds produced by the phytopathogenic bacterium Xanthomonas campestris pv. vesicatoria 85-10

Abstract: Xanthomonas campestrisis a phytopathogenic bacterium and causes many diseases of agricultural relevance. Volatiles were shown to be important in inter- and intraorganismic attraction and defense reactions. Recently it became apparent that also bacteria emit a plethora of volatiles, which influence other organisms such as invertebrates, plants and fungi. As a first step to study volatile-based bacterial–plant interactions, the emission profile ofXanthomonas c. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 73 publications
(88 reference statements)
2
49
0
Order By: Relevance
“…Currently, most studies on microbial volatiles are performed in vitro under nutrient rich conditions (Kai et al, 2009;Weise et al, 2012) and may not represent the conditions that prevail in the microbial environment. Furthermore, as indicated by Garbeva et al (2014a,b), the composition of volatiles produced by a mixture of bacterial species can differ from those produced by each bacterial monoculture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, most studies on microbial volatiles are performed in vitro under nutrient rich conditions (Kai et al, 2009;Weise et al, 2012) and may not represent the conditions that prevail in the microbial environment. Furthermore, as indicated by Garbeva et al (2014a,b), the composition of volatiles produced by a mixture of bacterial species can differ from those produced by each bacterial monoculture.…”
Section: Discussionmentioning
confidence: 99%
“…Because the production of volatiles is often reported to vary depending on cell density (Weise et al, 2012;Groenhagen et al, 2013), it is tempting to reason that volatiles are regulated by QS. However, there are only few and contradictory reports regarding QS regulation of volatile production.…”
Section: Discussionmentioning
confidence: 99%
“…The PGP effects were largely attributed to two volatiles, namely, 3-hydroxybutan-2-one (acetoin) and 2,3-butanediol. Several other studies have examined bacterial bioactive volatile compounds that promote or suppress plant growth (Farag et al, 2006;Splivallo et al, 2007;Vespermann et al, 2007;Kai et al, , 2010Gutiérrez-Luna et al, 2010;Zou et al, 2010;Blom et al, 2011aBlom et al, , 2011bVelazquez-Becerra et al, 2011;Weise et al, 2012;Yu and Lee, 2013), but the underlying mechanisms of these effects remain largely unknown (Wenke et al, 2012b). Profiling studies in Arabidopsis seedlings provided the first insights into changes in the transcriptome and proteome elicited by exposure to bacterial VOCs (Zhang et al, 2007;Kwon et al, 2010) and revealed the importance of hormone signaling, particularly that of indole-3-acetic acid and abscisic acid (Zhang et al, 2007(Zhang et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that bacterial volatiles can inhibit the growth of fungi or bacteria (Wrigley 2004;Kai et al 2007;Vespermann et al 2007;Zou et al 2007;Weise et al 2012;Garbeva et al 2014b) and in some cases they can even function as growth-promoting agent (Wheatley 2002;Horii & Ishii 2006;Garbeva et al 2014a). Additionally, volatiles emitted by bacteria can influence the metabolism of other surrounding bacteria Garbeva et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies, however, are performed in vitro on semi-solid media using nutrient rich conditions and may not represent the natural conditions in the microbial environment. Culture conditions including nutrient availability Insam & Seewald 2010) and the type of incubation medium substantially affect the spectrum of released VOCs (Weise et al 2012). Thus, bacteria produce a different set of volatiles when incubated in soil as compared to incubations on agar plates (Garbeva et al 2014b).…”
Section: Introductionmentioning
confidence: 99%